Correlation Analysis of Serum Vitamin D Levels and Postoperative Cognitive Disorder in Elderly Patients With Gastrointestinal Tumor - Zhang, Jialei; Zhang, Xiaoling; Yang, Yongyan; Zhao, Jun; Yu, Yonghao (Frontiers in Psychiatry, 2022)
Abstract Purpose: Vitamin D prevents hypocalcaemia, osteoporosis, and infections, among other problems, and is involved in the prevention and treatment of cardiovascular and neurological diseases. Recently, vitamin D was shown to improve cognitive dysfunction caused by Alzheimer's disease and vascular dementia. This study aims to explore the correlation between preoperative serum vitamin D and postoperative cognitive disorder (POCD) occurrence in elderly patients with gastrointestinal tumours to guide perioperative medication use and promote early patient recovery. Methods: This study recruited 238 elderly patients（65 ≤ age ≤ 85) who underwent gastrointestinal tumour surgery; 117 cases were enrolled, and 55 controls of the same age and education level as the cases were included. Blood samples were taken preoperatively and at 7, 15, 30, and 90 days postoperatively, and plasma vitamin D (25OH-D3) and glutathione (GSH) was measured. Different from the previous diagnosis of PND was obtained by telephone interview through Cognitive Status Modified Telephone Interview (TICS-m), mainly for memory impairment, a series of neuropsychological tests were used to evaluate cognitive function, Picture Recollect Test, Stroop Colour-word Test, and Digit Symbol Substitution Test were used to comprehensively evaluate the three domains of cognitive function of patients, namely memory, attention and information processing ability. All neuropsychiatric assessments were performed at the bedside and completed face-to-face by the assessment staff and the patient. Results: A total of 65.8% (77/117) of elderly patients undergoing gastrointestinal tumour surgery had preoperative vitamin D deficiency (serum 25OH-D concentration <12 ng/ml), of whom 46.7% (36/77, 7 days after surgery), 31.2% (24/77, 15 days after surgery), 15.6% (12/77, 30 days after surgery), and 9% (7/77, 90 days after surgery) of patients developed PNDs; 7.5% (3/40) of patients without vitamin D deficiency developed PNDs, which was detected only on the 7th day after surgery. Conclusions: Vitamin D deficiency can increase neurocognitive disorder risk in elderly patients during the perioperative period, possibly because low vitamin D levels cannot effectively inhibit the postoperative oxidative stress increase.